Estresse em enfermeiros com atuação em Unidade de Terapia Intensiva - Cavalheiro, Ana Maria [UNIFESP] (2008)
Purpose: The objective of this study was to evaluate stress and its intensity in nurses who work in intensive care units. We analyzed their clinical symptoms and identified the stressing factors’ influence in the health of these professionals. Methods: This was a transversal study including seventy five nurses. The data was collected by questionnaire; including information about stress factors (stress score) and clinical symptoms (clinical symptoms score). The statistical analyses were performed using Pearson correlation coeficients and adjusted linear modeling. A p value <0.05 was used to declare statistical significance. Results: The nurses had a moderate intensity of stress. Those professionals that were dissatisfied with their work presented on average 8.34 points more in the clinical symptoms score than those nurses who were not dissatisfied. Each point in the critical situations score corresponds to an increase of 0.62 points in the clinical symptoms score. This last score refers to cardiovascular, gastro-intestinal and muscular-skeletal changes. Conclusion: The nurses who work in intensive care units had moderate intensity of stress, according to the questionnaire used in this study. The clinical symptoms are positively related to the stress factors and to the intensity of stress. The stress factors and the clinical symptoms are associated with work dissatisfaction.